DESENVOLVIMENTO DE SOBREMESAS COM A INSERÇÃO DE PLANTAS ALIMENTÍCIAS NÃO CONVENCIONAIS (PANC) - DE MELO, PAULO HENRIQUE SOUZA (2024)
The search for food influenced human evolution, with discoveries such as the use of fire and the development of iron tools, which advanced both cuisine and human cognitive progress. Over time, food became more than a physiological necessity, turning into a source of comfort and pleasure, as well as an important cultural element. Although the biodiversity of edible plants is vast — potentially reaching up to 30,000 species — the number of plants actually consumed has decreased over time. In Brazil, only a fraction of this richness is exploited for human consumption, highlighting unfulfilled potential. Non-Conventional Edible Plants (PANC) are plant species, both native and exotic, whose edible parts are underutilized due to lack of knowledge or tradition. Often regarded as weeds or invasive plants, PANC have notable characteristics, such as spontaneous growth, adaptability, and low environmental impact. Despite their potential, PANC are underexplored commercially, representing an important opportunity for diversifying and ensuring food security. With this in mind, the intention is to develop desserts incorporating PANC, highlighting their value and benefits. For execution, a qualitative action research was conducted with a bibliographic review on PANC, addressing their origins, names, and uses. After acquiring the ingredients from the local market in João Pessoa and sourcing the PANC from local producers, the recipes were adjusted to include these species. Ten preparations were developed that encompass the foundations of pastry. All formulations demonstrate the feasibility of incorporating PANC into pastry, showing potential for commercial valorization, offering new flavor combinations, and a viable alternative for professional menus. Additionally, PANC provide nutritional diversity, sustainability, and authenticity, aligning with trends such as Slow Food and the appreciation of local ingredients. The introduction of these plants in pastry preparations can significantly contribute to culinary innovation, the preservation of food traditions, and the reduction of artificial food coloring.